Chromosomal-level assembly of yellow catfish genome using third-generation DNA sequencing and Hi-C analysis - Gong, Gaorui; Dan, Cheng; Xiao, Shijun; Guo, Wenjie; Huang, Peipei; Xiong, Yang; Wu, Junjie; He, Yan; Zhang, Jicheng; Li, Xiaohui; Chen, Nansheng; Gui, Jian-Fang; et al. (Gigascience, 2018)
The yellow catfish, Pelteobagrus fulvidraco, belonging to the Siluriformes order, is an economically important freshwater aquaculture fish species in Asia, especially in Southern China. The aquaculture industry has recently been facing tremendous challenges in germplasm degeneration and poor disease resistance. As the yellow catfish exhibits notable sex dimorphism in growth, with adult males about two- to three-fold bigger than females, the way in which the aquaculture industry takes advantage of such sex dimorphism is another challenge. To address these issues, a high-quality reference genome of the yellow catfish would be a very useful resource. To construct a high-quality reference genome for the yellow catfish, we generated 51.2 Gb short reads and 38.9 Gb long reads using Illumina and Pacific Biosciences (PacBio) sequencing platforms, respectively. The sequencing data were assembled into a 732.8 Mb genome assembly with a contig N50 length of 1.1 Mb. Additionally, we applied Hi-C technology to identify contacts among contigs, which were then used to assemble contigs into scaffolds, resulting in a genome assembly with 26 chromosomes and a scaffold N50 length of 25.8 Mb. Using 24,552 protein-coding genes annotated in the yellow catfish genome, the phylogenetic relationships of the yellow catfish with other teleosts showed that yellow catfish separated from the common ancestor of channel catfish ∼81.9 million years ago. We identified 1,717 gene families to be expanded in the yellow catfish, and those gene families are mainly enriched in the immune system, signal transduction, glycosphingolipid biosynthesis, and fatty acid biosynthesis. Taking advantage of Illumina, PacBio, and Hi-C technologies, we constructed the first high-quality chromosome-level genome assembly for the yellow catfish P. fulvidraco. The genomic resources generated in this work not only offer a valuable reference genome for functional genomics studies of yellow catfish to decipher the economic traits and sex determination but also provide important chromosome information for genome comparisons in the wider evolutionary research community.